Integrated 16S rRNA sequencing and metabolomics analysis to investigate the antidepressant role of Yang-Xin-Jie-Yu decoction on microbe-gut-metabolite in chronic unpredictable mild stress-induced depression rat model - Liang, Xing-Qiu; Mai, Peng-Yu; Qin, Hui; Li, Sen; Ou, Wen-Juan; Liang, Jian; Zhong, Jing; Liang, Ming-Kun (Frontiers in Pharmacology, 2022)
Objectives: Our goals were to evaluate the antidepressant efficacy of Yang-Xin-Jie-Yu Decoction (YXJYD) in Chronic Unpredictable Mild Stress (CUMS)-induced depression rat model and to investigate the underlying mechanisms. Design: We used CUMS-induced depression rat model to evaluate whether oral administration of YXJYD with different doses (2.1 g/kg, 1.05 g/kg and 0.525 g/kg, respectively) improve the depressive-like symptoms, and then performed UHPLC-Q-TOF-MS to explore the active ingredients of YXJYD. Subsequently, rat’s cecal contents, serum, and urine were collected from the control group, CUMS model group, and YXJYD high-dose (2.1 g/kg) treatment group. The 16S rRNA sequencing was performed on the cecal contents, based on Illumina MiSeq platform, and ANOVA analysis were used to analyze the composition variety and screen differential expression of gut bacteria in the three groups. 1H Nuclear Magnetic Resonance (NMR) analysis was used for analyzing the metabolites obtained from cecal contents, serum, and urine, and KEGG enrichment analysis was used to identify pathways of differential metabolites. An integrated 16S rRNA sequencing and metabolomic data were conducted to characterize the underlying mechanisms of YXJYD Results: The gut microbial communities, and serum, cecal content, urine metabolic compositions were significantly significantly altered in CUMS-induced depressive rats, while YXJYD effectively ameliorated the CUMS-associated gut microbiota dysbiosis, especially of Monoglobus, and alleviated the disturbance of serum, cecal content, urine metabolome and reversed the changes of key depressive and gut microbiota-related metabolites, such as succinic acid, taurine, hippuric acid, melatonin. With an integrated study of the gut microbiota and metabolomes, we identified the pathway of tricarboxylic acid cycle (TCA cycle) and propanoate metabolism as the regulated target of YXJYD on host-microbiome interaction. Conclusion: Our findings further confirmed the imbalance of metabolism and intestinal microbial is closely related to CUMS-induced depression. YXJYD regulates gut microbiome to affect body metabolomes and then produce antidepressant-like effect in CUMS-induced depressive rats while its molecular mechanism possibly be increased Monoglobus abundance in gut microbiota and regulated the TCA cycle pathway and propanoate metabolism in host.